BETON SELF COMPACTING CONCRETE DENGAN SERBUK KACA - Roderick Afta; Istiqomah Istiqomah; Ben Novarro Batubara (Universitas Pendidikan Indonesia (UPI), 2021)
Self Compacting Concrete (SCC) is commonly referred to as flowing concrete because it has a high slump specification with a slump value of more than 19 cm (ASTM C 1017). Self-compacting concrete has been widely used in the construction world because it has several advantages, such as increasing workability. The high workability of SCC concrete is due to the use of superplasticizer added materials that are mixed into the concrete. With the addition of a superplasticizer, it can improve the workability of the concrete mix. So that SCC concrete has a low water-cement factor, SCC concrete is easier to work with when compared to normal concrete. In this study, the addition of the percentage of glass powder started from 0%, 2.5%, 5%, 7.5%, 10% and 12.5% with a 1.5% superplasticizer. Strength growth from each time difference of the concrete compressive test has increased the value of the compressive strength, the percentage increase in the average compressive strength test results. At the age of seven days the average compressive strength of concrete reaches 87.16%, while at 14 days the average compressive strength of concrete reaches 93.39%, and at 28 days the average compressive strength of concrete reaches 100%. The addition of glass powder to SCC concrete generally shows an increase in compressive strength. The highest average compressive strength was at 7.5% glass powder with 1.5% superplasticizer with a compressive strength of 7, 14, and 28 days, respectively, which was 48.80 MPa, 52.41 MPa, and 56.19 MPa. The level of addition of glass powder for SCC concrete based on the calculation of the maximum use of glass powder is 7.5% by weight of cement with a superplasticizer content of 1.5%Keywords: Concrete Mix, Flowing Concrete, Self Compacting Concrete, Strength, Superplasticizer